High and low temperature self-adaptive foaming ceramic castable and preparation method thereof
By using high-temperature foamed ceramic balls and hollow alumina spheres in ceramic castables, a porous structure is constructed and expanded at high temperatures, the problem of sintering and shrinking of ceramic castables in high-temperature environments is solved, efficient heat insulation and sealing effects are achieved, and the temperature resistance and service life of the electromagnetic coil is improved.
Patent Information
- Application Number
- CN202411894395.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
AI Technical Summary
Existing ceramic castables are prone to sintering and shrinking in high temperature environments, resulting in difficulty in ensuring density, micropore effect and strength at the sealing joint, and are unable to be suitable for electromagnetic coil packaging in high temperature environments.
Adaptive foamed ceramic castables of high and low temperatures, which include high-temperature foamed ceramic balls and hollow alumina spheres. The frame is constructed by stacking microspheres of different sizes to increase porosity and reduce thermal conductivity. The high-temperature foamed ceramic balls foam and expand at high temperatures, and the low-melting point glass powder coating melts and blocks the pores, reducing volume shrinkage and enhancing the heat insulation effect.
In the interval of 200-450℃, the ceramic castable forms a porous structure, reduces the thermal conductivity, improves the temperature resistance level and service life; in the interval of 500-1000℃, the high-temperature foamed ceramic balls of the ceramic castable expand, enhances the insulation effect, reduces volume shrinkage, and ensures the strength at the seal joint and the safety of the use of the electromagnetic coil.
Smart Images

Figure BDA0005201344320000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of castables, in particular to a high-low temperature self-adaptive foamed ceramic castable and a preparation method thereof. Background Art
[0002] With the development of science and technology, the temperature resistance requirements for electromagnetic coil assemblies (including coil skeletons, winding wires, lead wires and castables, etc.) used for electromagnetic conversion, analog signal transmission, electric pulses and control current on equipment such as aerospace engines, nuclear power, excitation coils and transformers have gradually increased. In order to improve the high-temperature insulation and stability of electromagnetic coil assemblies, the improvement of heat resistance mainly involves two aspects. The first aspect is to improve the temperature resistance of electromagnetic wires. At present, a large number of studies have been carried out at home and abroad on electromagnetic coil conductors and insulation materials, which have basically reached the requirements of long-term stable operation at temperatures of 400°C and above. The second aspect is to improve the temperature resistance of coil castables. The use of castable encapsulation can improve the temperature resistance of encapsulated coil assemblies and can provide certain protection for electromagnetic coils.
[0003] At present, thermosetting plastics such as phenolic plastics, amino plastics, epoxy resins, DAP (diallyl phthalate), DMC (unsaturated polyester bulk molding compound), polystyrene and other organic materials are commonly used at home and abroad, which are only suitable for encapsulating electromagnetic coils and skeletons used in low-temperature environments below 300°C. Compared with organic castables, inorganic castables have better high-temperature insulation and thermal stability. They complete the glass or ceramic transition under high temperature conditions to achieve the purpose of high temperature resistance. However, this type of castable has problems such as poor thermal insulation performance, large shrinkage rate and easy cracking due to improper selection of main components such as skeletons, fillers, and binders.
[0004] Foamed ceramic castable is a ceramic material with a porous structure formed after sintering and foaming. It is a multifunctional material that integrates high porosity, high specific surface area, low volume shrinkage, low thermal conductivity and other properties. It also has the inherent properties of ceramic materials such as high temperature resistance, acid and alkali resistance, long life, and high strength.
[0005] The current preparation processes of foamed ceramic castables include direct foaming, in-situ foaming, pore-making, template replication and particle stacking sintering. In the in-situ foaming method, the foaming agent in the raw material reacts with oxygen in the air and oxygen in the ceramic matrix to produce gas, which is then wrapped in the ceramic matrix to form closed or interconnected pores to form foamed ceramics. Different ambient temperatures will have a significant impact on the pore size, shrinkage and strength of the foamed ceramics. Electromagnetic coils may face variable temperature environments during actual applications. When faced with overheating, the ceramic castable will sinter and shrink, making it difficult to effectively ensure its density, microporous effect and strength at the joint with the seal.
[0006] The Chinese patent application with publication number CN118812240 A discloses a method for preparing a novel foamed ceramic, wherein the materials used for preparation are as follows by weight: 5-10 parts of bentonite; 15-25 parts of perlite tailings; 15-30 parts of foamed pressed mud; 20-40 parts of feldspar tailings; 20-30 parts of at least one of magnesium slag, chromium slag, and manganese slag; 0.2-0.3 parts of silicon carbide; and 0.2-3.0 parts of at least one of copper oxide, manganese oxide, chromium oxide, and iron oxide. The patent can effectively make the foamed ceramic achieve a microporous effect by adding at least one of copper oxide, manganese oxide, chromium oxide, and iron oxide, but the foaming temperature is relatively high, so it cannot be used for the packaging of electromagnetic coils.
[0007] The Chinese patent application with publication number CN118290170 A discloses a high-strength poly-light mullite microporous castable and its preparation method. The castable raw material weight parts are as follows: 20-50 parts of poly-light mullite microporous homogenizing material, 20-45 parts of light-burned mullite material, 20-30 parts of bauxite powder, 5-10 parts of silica powder, 2-8 parts of calcium aluminate cement, 3-10 parts of kyanite, and 0.2-1.0 parts of water reducing agent. The castable has a micropore diameter of up to nanometer level, and has the characteristics of light weight, high strength, and strong anti-corrosion ability, but also has the problems of high foaming temperature and high thermal conductivity. The Chinese patent application with publication number CN101792294A discloses a lightweight insulating refractory castable, which includes the following components in weight percentage: chemically modified lightweight aggregate: 40-60%; fused mullite (0-1mm): 10-20%; kyanite powder (particle size 180 mesh): 5-10%; first-grade high-alumina bauxite clinker powder (particle size 180 mesh): 5-10%; silicon dioxide powder (particle size ≤5μm): 3-8%; α-Al2O3 powder (particle size ≤5μm): 3-8%; high-alumina cement: 5-10%; zirconium-containing high-alumina refractory fiber: 0.5-10%; heat-resistant steel fiber: 1.5-4%; melamine: 0.1-1%; organic explosion-proof fiber: 0.05-0.10%. This patent application reduces the thermal conductivity of the castable by using lightweight aggregates, and significantly improves the mechanical properties and service life of the lightweight castable by chemically improving the lightweight aggregates. However, due to the use of steel fibers as a means of reinforcement and toughening, during high-temperature use, the steel fibers are prone to high-temperature oxidation expansion and brittle failure, and the high-temperature performance of the castable is degraded through high-temperature reactions of oxidation products with the refractory castable.
[0008] In view of the above problems, it is of great significance to develop a high and low temperature adaptive foamed ceramic castable. Summary of the invention
[0009] In view of the problems existing in the prior art, the high and low temperature adaptive foamed ceramic castable provided by the present invention includes high-temperature foamed ceramic ball filler. After curing, the ceramic castable can be combined with the electromagnetic coil to form an integral structure, showing good sealing performance. In the range of 200-450°C, the ceramic castable foams to form a porous structure, which reduces the thermal conductivity of the electromagnetic coil and improves the temperature resistance level and service life of the electromagnetic coil to a certain extent. When the ambient temperature is 500-1000°C, the high-temperature foamed ceramic ball filler in the ceramic castable will gradually foam and transform into porous microspheres, enhancing the thermal insulation effect and reducing volume shrinkage, which can effectively prevent the spread of cracks at the sealing joint and ensure the safety of the electromagnetic coil in this temperature range.
[0010] To achieve this object, the present invention adopts the following technical solutions:
[0011] The first aspect of the present invention provides a high and low temperature adaptive foamed ceramic castable, comprising the following components by mass percentage: 30% to 45% of high temperature foamed ceramic balls, 10% to 25% of hollow alumina balls, 10% to 25% of mullite aggregate, 1% to 5% of silicon micropowder, 1% to 5% of magnesium oxide micropowder, 1% to 5% of alumina micropowder, 3% to 8% of modified short chopped alumina fiber, 1% to 5% of kyanite powder, 1% to 3% of talc fine powder, and nano silicon dioxide. Aerogel powder 1%-3%, bauxite powder 1%-5%, calcium aluminate cement powder 2%-5%, mullite microporous homogenizer 1%-5%, phosphate binder 0.5%-0.8%, fly ash 0.5%-1%, dispersant 0.5%-1%, composite water reducer 0.5%-1%, expansion agent 1%-5%, foaming agent 1%-3%, foaming promoter 0.1%-0.5%, nano alumina sol 10%-30%, water 10%-20%.
[0012] In some embodiments of the present invention, the high-temperature foamed ceramic ball includes a high-temperature foamed ceramic ball core and a low-melting point glass powder coating coated on the surface of the high-temperature foamed ceramic ball core. When the ambient temperature is lower than 500°C, the structure is stable. When the ambient temperature is higher than 500°C, the high-temperature foamed ceramic ball core can foam and expand into porous microspheres, and the low-melting point glass powder coating melts and blocks the pores on the surface of the porous microspheres.
[0013] In some embodiments of the present invention, the particle size of the high temperature foamed ceramic balls is 1 to 6 mm, and can be 1 to 2 mm, 2 to 3 mm, 3 to 4 mm, 4 to 5 mm, or 5 to 6 mm.
[0014] In some embodiments of the present invention, the method for preparing the high temperature foamed ceramic ball comprises the following steps:
[0015] S1. Take 40% to 75% of refractory aggregate, 25% to 45% of reinforcing agent, 10% to 15% of adhesive, 2% to 5% of plasticizer, 1% to 3% of dispersant, 1% to 3% of foaming agent, and 1% to 5% of expansion agent by mass percentage, mix well, and obtain dry material;
[0016] S2, adding water to the dry material, granulating, and obtaining a ceramic ball body;
[0017] S3, air-drying and solidifying the ceramic ball blank, and screening to obtain a prefabricated ceramic ball blank;
[0018] S4, coating the surface of the prefabricated ceramic ball blank with a low melting point glass powder coating, sintering, and slowly cooling to obtain a high temperature foamed ceramic ball.
[0019] The second aspect of the present invention provides a method for preparing a high and low temperature adaptive foamed ceramic castable, comprising the following steps:
[0020] Step 1: high temperature foamed ceramic balls, hollow alumina balls, mullite aggregate, silicon powder, magnesium oxide powder, alumina powder, modified chopped alumina fiber, kyanite powder, talc powder, bauxite powder, and calcium aluminate cement powder are mixed in proportion and stirred evenly to obtain a mixed dry material;
[0021] Step 2: Mix the nano-alumina sol, water and nano-silicon dioxide aerogel powder in proportion, and stir evenly to obtain a mixed liquid;
[0022] Step 3: under stirring conditions, the mixed dry material obtained in step 1, mullite microporous homogenizing material, phosphate binder, fly ash, dispersant, composite water reducing agent, expansion agent, foaming agent, and foaming promoter are sequentially added to the mixed liquid obtained in step 2, and stirred evenly to obtain a fluid casting material;
[0023] Step 4: pour the flowing casting material obtained in step 3 into the electromagnetic coil skeleton to encapsulate the coil, solidify, dry and foam, and obtain the encapsulated casting material.
[0024] A third aspect of the present invention provides an electromagnetic coil which is packaged with the above-mentioned high and low temperature adaptive foamed ceramic casting material.
[0025] In some embodiments of the present invention, the electromagnetic coils include nuclear power control rod drive mechanism electromagnetic coils, aerospace engine electromagnetic coils, excitation coils, and aerospace sensor electromagnetic coils.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The high and low temperature adaptive foamed ceramic castable provided by the present invention uses high-temperature foamed ceramic balls and hollow alumina balls as fillers, and microspheres of different sizes are stacked to construct a skeleton, thereby increasing the porosity of the castable. The hollow alumina balls and the internal hollow structure increase the number of closed pores in the castable, which can effectively reduce the thermal conductivity of the castable and improve the thermal insulation performance and thermal shock resistance of the castable. When the temperature is high, the low-melting-point glass powder ceramic coating on the surface of the high-temperature foamed ceramic balls melts to form a liquid phase with appropriate viscosity. The liquid phase can effectively block the pores on the surface of the high-temperature foamed ceramic balls and prevent the escape of internal gas, which can further increase the thermal conductivity of the castable. In addition, due to the volume expansion of the high-temperature foamed ceramic balls, the overall volume shrinkage of the castable is reduced, thereby ensuring the strength of the castable and preventing the generation of cracks at the sealed joint.
[0028] 2. The high and low temperature adaptive foamed ceramic castable provided by the present invention has mullite that can fill the gaps between the skeletons constructed by high-temperature foamed ceramic balls and hollow alumina balls, silicon micropowder, magnesium oxide micropowder and alumina micropowder that can improve the fluidity of the castable, alumina fiber that plays a role in strengthening and toughening, kyanite powder that improves the high-temperature volume stability of the castable, talc fine powder that increases the density of the castable, nano-silica aerogel powder that reduces the thermal conductivity of the castable, bauxite powder, calcium aluminate cement, phosphate binder and fly ash that can improve the high-temperature strength of the castable, dispersant that promotes uniform dispersion of each component, and synergistically improves the fluidity of the castable with the composite water reducer and alumina sol, and the raw materials of each component cooperate with each other and synergistically enhance the effect, thereby giving the castable excellent mechanical strength, thermal insulation performance and high-temperature performance. DETAILED DESCRIPTION
[0029] The high and low temperature self-adaptive foamed ceramic castable and its preparation method of the present invention are described in detail below.
[0030] The inventor of the present invention constructs a stacked skeleton by mixing high-temperature foamed ceramic balls and hollow alumina balls of different particle sizes, and the synergistic effect of mullite aggregate and other components makes the castable have good mechanical properties and thermal insulation properties. The low-melting-point glass powder ceramic coating on the surface of the high-temperature foamed ceramic balls melts under high-temperature conditions to form a liquid phase with appropriate viscosity, which can effectively block the pores on the surface of the high-temperature foamed ceramic balls and prevent the escape of internal gas. The volume of the high-temperature foamed ceramic balls expands, reducing the overall volume shrinkage of the castable, thereby ensuring the strength of the castable and inhibiting the generation and spread of cracks at the sealing joint, so that the castable has good high-temperature performance. The present invention is completed on this basis.
[0031] The first aspect of the present invention provides a high and low temperature adaptive foamed ceramic castable, comprising the following components by mass percentage: 30% to 45% of high temperature foamed ceramic balls, 10% to 25% of hollow alumina balls, 10% to 25% of mullite aggregate, 1% to 5% of silicon micropowder, 1% to 5% of magnesium oxide micropowder, 1% to 5% of alumina micropowder, 3% to 8% of modified short chopped alumina fiber, 1% to 5% of kyanite powder, 1% to 3% of talc fine powder, and nano silicon dioxide. Aerogel powder 1%-3%, bauxite powder 1%-5%, calcium aluminate cement powder 2%-5%, mullite microporous homogenizer 1%-5%, phosphate binder 0.5%-0.8%, fly ash 0.5%-1%, dispersant 0.5%-1%, composite water reducer 0.5%-1%, expansion agent 1%-5%, foaming agent 1%-3%, foaming promoter 0.1%-0.5%, nano alumina sol 10%-30%, water 10%-20%.
[0032] In some embodiments of the present invention, the high-temperature foamed ceramic ball includes a high-temperature foamed ceramic ball core and a low-melting point glass powder coating coated on the surface of the high-temperature foamed ceramic ball core. When the ambient temperature is lower than 500°C, the structure is stable. When the ambient temperature is higher than 500°C, the high-temperature foamed ceramic ball core can foam and expand into porous microspheres, and the low-melting point glass powder coating melts and blocks the pores on the surface of the porous microspheres.
[0033] In some embodiments of the present invention, the particle size of the high temperature foamed ceramic balls is 1 to 6 mm, and can be 1 to 2 mm, 2 to 3 mm, 3 to 4 mm, 4 to 5 mm, or 5 to 6 mm.
[0034] In some embodiments of the present invention, the method for preparing the high temperature foamed ceramic ball comprises the following steps:
[0035] S1. Take 40% to 75% of refractory aggregate, 25% to 45% of reinforcing agent, 10% to 15% of adhesive, 2% to 5% of plasticizer, 1% to 3% of dispersant, 1% to 3% of foaming agent, and 1% to 5% of expansion agent by mass percentage, mix well, and obtain dry material;
[0036] S2, adding water to the dry material, granulating, and obtaining a ceramic ball body;
[0037] S3, air-drying and solidifying the ceramic ball blank, and screening to obtain a prefabricated ceramic ball blank;
[0038] S4, coating the surface of the prefabricated ceramic ball blank with a low melting point glass powder coating, sintering, and slowly cooling to obtain a high temperature foamed ceramic ball.
[0039] In some embodiments of the present invention, the refractory aggregate is selected from any one or more of kaolin, mullite, and high-alumina bauxite.
[0040] In some embodiments of the present invention, the reinforcing agent is selected from any one or more of silicon micropowder, aluminum oxide micropowder, and zirconium oxide micropowder; the SiO2 content of the silicon micropowder is ≥90wt%, and the particle size is 5 to 10μm; the MgO content of the magnesium oxide micropowder is ≥90wt%, and the particle size is 5 to 10μm; the ZrO content of the zirconium oxide micropowder is ≥90wt% and the particle size is 5 to 10μm.
[0041] In some embodiments of the present invention, the adhesive is selected from any one or more of Portland cement, alumina cement, magnesia cement, and water glass.
[0042] In some embodiments of the present invention, the plasticizer is selected from any one or more of montmorillonite clay, bentonite, and high-iron clay.
[0043] In some embodiments of the present invention, the dispersant is selected from any one or more of triethylhexyl phosphoric acid and sodium dodecyl sulfate.
[0044] In some embodiments of the present invention, the foaming agent is selected from any one or more of calcium carbonate, sodium carbonate, potassium carbonate and sodium chloride.
[0045] In some embodiments of the present invention, the expansion agent is selected from any one or more of silica powder, kyanite powder, and clay.
[0046] In some embodiments of the present invention, in S2, the mass of the water added is 35% to 55% of the total mass of the dry material obtained in S1.
[0047] In some embodiments of the present invention, in S2, the granulation can be carried out by any one of an extrusion granulator, a drum granulator, and a spray drying granulator.
[0048] In some embodiments of the present invention, in S3, the particle size of the sieving is required to be 1 to 6 mm.
[0049] In some embodiments of the present invention, in S4, the components of the low-melting-point glass powder coating include SiO2, P2O5, B2O3, Li2O, ZnO, BaO, K2O, and Na2O, with a melting point of 500-800°C, which can be 500-600°C, 600-700°C, or 700-800°C; the thickness is 30-80 μm, which can be 30-40°C, 40-50°C, 50-60°C, 60-70°C, or 70-80°C.
[0050] In some embodiments of the present invention, in S4, the sintering temperature is 450-500°C, which can be 450-460°C, 460-470°C, 470-480°C, 480-490°C, or 490-500°C; the sintering time is 3-6h, which can be 3-4h, 4-5h, or 5-6h.
[0051] In some embodiments of the present invention, the Al2O3 content of the hollow alumina sphere is ≥95wt%, and the sphere diameter is 0.5-1mm. The present invention uses high-temperature foamed ceramic spheres and hollow alumina spheres as fillers, and stacks microspheres of different sizes to construct a skeleton, thereby increasing the porosity of the castable, and because the hollow alumina spheres and the internal hollow structure increase the number of closed pores in the castable, the thermal conductivity of the castable can be effectively reduced, and the thermal insulation performance and thermal shock resistance of the castable can be improved.
[0052] In some embodiments of the present invention, the particle size of the mullite aggregate is 2 to 3 mm, and the average pore size of the micropores is ≤ 5 μm. By using the mullite aggregate, the gaps between the alumina hollow spheres and the high-temperature foamed ceramic sphere aggregates can be filled by utilizing the irregular shape and interlaced lamellar crystal structure of the aggregate itself, thereby improving the mechanical properties and high-temperature volume stability of the castable, and further reducing the thermal conductivity of the castable through its microporous structure.
[0053] In some embodiments of the present invention, the SiO2 content of the silicon micropowder is ≥90wt%, and the particle size is 5-10μm. In some embodiments of the present invention, the MgO content of the magnesium oxide micropowder is ≥90wt%, and the particle size is 5-10μm. In some embodiments of the present invention, the Al2O3 content of the alumina micropowder is ≥90wt%, the particle size is 5-10μm, and the crystal phase is α-Al2O3. By adding silicon micropowder, magnesium oxide micropowder, and aluminum oxide micropowder, the fluidity of the castable is improved and the heat resistance of the castable is increased.
[0054] In some embodiments of the present invention, the length of the modified short alumina fiber is 2 to 3 mm, and the surface is modified by KH-560 silane coupling agent. The addition of alumina fiber has a reinforcing and toughening effect on the castable. The surface modification of alumina fiber by KH-560 silane coupling agent improves the interface compatibility between alumina fiber and castable.
[0055] In some embodiments of the present invention, the particle size of the kyanite powder is 0.5-1 mm. The addition of the kyanite powder improves the high-temperature volume stability of the castable and avoids cracking and breakage caused by high-temperature shrinkage.
[0056] In some embodiments of the present invention, the particle size of the talc powder is 10-30 μm. The addition of talc powder can not only improve the early strength of the castable after solidification, but also fill the pores of the castable and increase the density of the castable, thereby effectively preventing the castable from cracking and shrinking.
[0057] In some embodiments of the present invention, the density of the nano-silicon dioxide aerogel powder is 0.03-0.08 g / cm 3 By adding nano-silica aerogel powder and utilizing its nano-scale pore size and ultra-low thermal conductivity, the thermal conductivity coefficient can be further reduced and the thermal insulation performance of the castable can be improved.
[0058] In some embodiments of the present invention, the Al2O3 content in the bauxite powder is ≥80wt%, and the particle size is 20-45μm. By adding the bauxite powder, the high temperature flexural strength, thermal shock resistance and bursting temperature resistance of the castable can be improved.
[0059] In some embodiments of the present invention, the calcium aluminate cement powder is obtained by high-purity calcium oxide and aluminum oxide through high-temperature sintering, and the content of aluminum oxide is 80-85%. By adding calcium aluminate cement, the early hydration reaction of the castable can be effectively controlled, and the early hardening rate of the castable can be slowed down, thereby improving the strength and durability of the castable.
[0060] In some embodiments of the present invention, the particle size of the mullite microporous homogenizing material is 5 to 10 μm.
[0061] In some embodiments of the present invention, the particle size of the phosphate binder is 0.2-0.5 mm. The use of the phosphate binder can accelerate the curing process of the castable, improve the strength of the castable, improve the fluidity of the castable and reduce the generation of castable cracks.
[0062] In some embodiments of the present invention, the particle size of the fly ash is 0.2-0.5 mm. The addition of fly ash further reduces the thermal conductivity, and when used at high temperature in a tunnel heating furnace, the fly ash partially undergoes liquid phase reaction due to the presence of low melting point impurities, which promotes sintering and improves the high temperature strength of the castable.
[0063] In some embodiments of the present invention, the dispersant is selected from one or a combination of triethylhexyl phosphate and sodium dodecyl sulfate. By adding the dispersant, the physical and chemical properties of the surface of the matrix particles can be changed, the repulsion between the particles can be increased, the fluidity of the castable can be improved, and its processability can be improved.
[0064] In some embodiments of the present invention, the composite water reducer is a mixture of sodium tripolyphosphate, sodium silicate and sodium hexametaphosphate, wherein the mass of sodium tripolyphosphate accounts for 40-60% of the total mass of the composite water reducer, the mass of sodium silicate accounts for 20-40% of the total mass of the composite water reducer, and the mass of sodium hexametaphosphate accounts for 10-30% of the total mass of the composite water reducer. By using the composite water reducer, the performance shortcomings of a single water reducer are avoided, the construction fluidity of the castable is improved, and the amount of water added to the castable is reduced, achieving the effect of both high water reduction rate and no segregation.
[0065] In some embodiments of the present invention, the swelling agent is selected from one or more combinations of wheat flour, bentonite and alum.
[0066] In some embodiments of the present invention, the foaming agent is selected from one or more combinations of zinc stearate, chromium stearate, and barium stearate.
[0067] In some embodiments of the present invention, the Al2O3 content in the alumina sol is 30% to 40%, and the pH value is 7.0 to 8.5. By adding alumina sol, the curing time of the material to meet the construction requirements can be effectively controlled by adjusting the pH value, so as to shorten the curing time and quickly demould. At the same time, the silica sol is hydrated and gelled and crystallized inside the material. The large number of micropores generated during molding can effectively discharge the water vapor generated during the rapid baking inside the material, so as to achieve the purpose of rapid drying and baking, and greatly shorten the production cycle of the furnace roller. In addition, compared with the cement bonding system, the silica sol bonding castable has good high temperature strength and thermal shock resistance. In addition, by adding alumina sol, the morphology and surface energy of the castable can also be changed, the friction between the castable filler particles can be reduced, the flowability of the castable can be increased, and the uniform pouring and filling of the castable can be promoted.
[0068] The second aspect of the present invention provides a method for preparing the above-mentioned high and low temperature adaptive foamed ceramic castable, comprising the following steps:
[0069] Step 1: high temperature foamed ceramic balls, hollow alumina balls, mullite aggregate, silicon powder, magnesium oxide powder, alumina powder, modified chopped alumina fiber, kyanite powder, talc powder, bauxite powder, and calcium aluminate cement powder are mixed in proportion and stirred evenly to obtain a mixed dry material;
[0070] Step 2: Mix the nano-alumina sol, water and nano-silicon dioxide aerogel powder in proportion, and stir evenly to obtain a mixed liquid;
[0071] Step 3: under stirring conditions, the mixed dry material obtained in step 1, mullite microporous homogenizing material, phosphate binder, fly ash, dispersant, composite water reducing agent, expansion agent, foaming agent, and foaming promoter are sequentially added to the mixed liquid obtained in step 2, and stirred evenly to obtain a fluid casting material;
[0072] Step 4: pour the flowing casting material obtained in step 3 into the electromagnetic coil skeleton to encapsulate the coil, solidify, dry and foam, and obtain the encapsulated casting material.
[0073] In some embodiments of the present invention, in step 1, the stirring is performed using a roller mixer, and the stirring time is 3 to 6 hours.
[0074] In some embodiments of the present invention, in step 2, the stirring is performed using a planetary mixer for 2 to 3 hours.
[0075] In some embodiments of the present invention, in step three, the stirring is performed using a planetary mixer, and the stirring time is 6 to 12 hours.
[0076] In some embodiments of the present invention, in step 4, the coagulation is carried out at room temperature and the coagulation time is 24 to 72 hours.
[0077] In some embodiments of the present invention, in step 4, the drying and foaming treatment is specifically to place the encapsulated coil in an oven for staged temperature increase heat treatment; preferably, the temperature of the oven is set at 80-120°C in the first stage, and the insulation time is 1.5-2h; the temperature of the oven is set at 150-200°C in the second stage, and the insulation time is 3-5h; the temperature of the oven is set at 250-300°C in the third stage, and the insulation time is 3-5h; the heating rate of the oven is not higher than 10°C / min.
[0078] A third aspect of the present invention provides an electromagnetic coil which is packaged with the above-mentioned high and low temperature adaptive foamed ceramic casting material.
[0079] In some embodiments of the present invention, the electromagnetic coils include electromagnetic coils of nuclear power control rod drive mechanisms, electromagnetic coils of aerospace engines, excitation coils, and electromagnetic coils of aerospace sensors, etc.
[0080] The high and low temperature adaptive foamed ceramic castable provided by the present invention has a stable structure when the ambient temperature is lower than 500°C and can ensure the packaging effect. When the ambient temperature is higher than 500°C, the high-temperature foamed ceramic ball core in the castable can foam and expand into porous microspheres, and the low-melting-point glass powder coating melts and blocks the pores on the surface of the porous microspheres to avoid sintering shrinkage, thereby effectively ensuring the volume density of the encapsulated castable, the micropore effect and the strength of the sealing joint.
[0081] The specific embodiments of the present invention are further described in detail below in conjunction with preferred embodiments. When the embodiments provide numerical ranges, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, as those skilled in the art grasp the prior art and record the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.
[0082] The raw material requirements used in the following examples are as follows:
[0083] The Al2O3 content of the alumina hollow sphere is ≥95wt% and the sphere diameter is 0.5-1mm;
[0084] The mullite aggregate particle size is 2 mm, and the average pore diameter is 1 to 5 μm;
[0085] The SiO2 content of silicon micropowder is ≥90wt% and the particle size is 5-10μm;
[0086] The MgO content of the magnesium oxide powder is ≥90wt% and the particle size is 5-10μm;
[0087] The Al2O3 content of the alumina powder is ≥90wt%, the particle size is 5-10μm, and the crystal phase is α-Al2O3;
[0088] The preparation method of the modified short-cut alumina fiber is to cut alumina fiber with an Al2O3 content of 80% and a diameter of 10-20 μm into short fibers with a length of 2-3 mm, and then use KH-560 silane coupling agent to spray on the surface of the short fibers for modification;
[0089] The particle size of kyanite powder is 0.5 to 1 mm;
[0090] The particle size of talc fine powder is 10 to 30 μm;
[0091] The density of nano-silica aerogel powder is 0.03~0.08g / cm 3 ;
[0092] The Al2O3 content in the bauxite powder is ≥80wt%, and the particle size of the bauxite powder is 20-45μm;
[0093] Calcium aluminate cement powder is made by sintering high-purity calcium oxide and aluminum oxide at high temperature, and the aluminum oxide content is 80-85%;
[0094] The particle size of the mullite microporous homogenized material is 5 to 10 μm;
[0095] The particle size of the phosphate binder is 0.2 to 0.5 mm;
[0096] The particle size of fly ash is 0.2-0.5 mm;
[0097] The dispersant is triethylhexyl phosphoric acid.
[0098] Example 1
[0099] In this embodiment, the composite water reducer is a mixture of sodium tripolyphosphate, sodium silicate and sodium hexametaphosphate, wherein the mass of sodium tripolyphosphate accounts for 40% of the total mass of the composite water reducer, the mass of sodium silicate accounts for 20% of the total mass of the composite water reducer, and the mass of sodium hexametaphosphate accounts for 20% of the total mass of the composite water reducer; the expansion agent is wheat flour; the foaming agent is zinc stearate; the foaming accelerator is a combination of stearic acid and lead phthalate; the Al2O3 content in the alumina sol is 30%, and the pH value is 7.0.
[0100] 1.1 Preparation of high temperature foamed ceramic balls
[0101] The preparation method of high temperature foamed ceramic balls is as follows:
[0102] S1. Take 55% kaolin, 30% silica powder, 10% silicate cement, 2% montmorillonite clay, 1% triethylhexyl phosphate, 1% mixture of calcium carbonate and sodium carbonate, and 1% silica powder by mass percentage, stir and mix well to obtain dry material;
[0103] S2, adding water with a weight of 35% of the total weight of the dry material to the dry material, and granulating it through an extrusion granulator to obtain a ceramic ball body;
[0104] S3, after the ceramic ball blank is air-dried and solidified, it is sieved using a sieve to obtain a prefabricated ceramic ball blank with a particle size of 1 mm;
[0105] S4. Coat a low-melting-point glass powder ceramic coating on the surface of the preformed ceramic ball blank, wherein the components of the low-melting-point glass powder coating include SiO2, P2O5, B2O3, Li2O, ZnO, BaO, K2O, and Na2O, with a melting point of 500°C and a thickness of 30 to 40 μm; then sinter at 450°C for 3 hours, slowly cool, and sieve to obtain a high-temperature foamed ceramic ball with a particle size of 1 to 3 mm.
[0106] 1.2 High and low temperature adaptive foamed ceramic castable
[0107] 1.2.1 Composition of high and low temperature adaptive foamed ceramic castables
[0108] The high and low temperature adaptive foamed ceramic castable includes the following components by mass percentage: 35% high temperature foamed ceramic balls, 10% alumina hollow balls, 10% mullite aggregate, 3% silica powder, 2% magnesium oxide powder, 13% alumina powder, 3% modified chopped alumina fiber, 2% kyanite powder, 2% talc powder, 1% nano silica aerogel powder, 1% bauxite powder, 2% calcium aluminate cement powder, 1% mullite microporous homogenizer, 0.5% phosphate binder, 0.5% fly ash, 1% dispersant, 0.5% composite water reducer, 1% expansion agent, 1% foaming agent, 0.5% foaming promoter, 10% nano alumina sol, and 10% water. 1.2.2 Preparation of high and low temperature adaptive foamed ceramic castable
[0109] The preparation method of high and low temperature adaptive foamed ceramic casting material comprises the following steps:
[0110] Step 1: Mix high-temperature foamed ceramic balls, hollow alumina balls, mullite aggregate, silicon powder, magnesium oxide powder, alumina powder, modified chopped alumina fiber, kyanite powder, talc powder, bauxite powder, and calcium aluminate cement powder in proportion, add them into a roller mixer and mix for 3 hours to obtain a mixed dry material.
[0111] Step 2: Mix the nano-alumina sol, water and nano-silicon dioxide aerogel powder in proportion, add the mixture into a planetary mixer and mix for 2 hours to obtain a mixed liquid;
[0112] Step 3: While the mixed solution in step 2 is being continuously stirred, the mixed dry material in step 1, the mullite microporous homogenizing material, the phosphate binder, the fly ash, the dispersant, the composite water reducing agent, the expansion agent, the foaming agent, and the foaming promoter are sequentially added to the mixed solution, and the mixture is continuously mixed for 6 hours in a planetary mixer to obtain a fluidized casting material;
[0113] Step 4: Pour the fluid casting material into the electromagnetic coil skeleton to encapsulate the coil, solidify it at room temperature for 24 hours, and place the encapsulated coil in an oven for drying and foaming. Specifically, the encapsulated coil is placed in an oven for segmented heating treatment. The temperature of the oven is set to 80°C in the first section, and the insulation time is 1.5h; the temperature of the oven is set to 150°C in the second section, and the insulation time is 3h; the temperature of the oven is set to 250°C in the third section, and the insulation time is 3h; the heating rate of the oven is 5°C / min; the encapsulated casting material is obtained.
[0114] Example 2
[0115] In this embodiment, the composite water reducer is a mixture of sodium tripolyphosphate, sodium silicate and sodium hexametaphosphate, wherein the mass of sodium tripolyphosphate accounts for 50% of the total mass of the composite water reducer, the mass of sodium silicate accounts for 25% of the total mass of the composite water reducer, and the mass of sodium hexametaphosphate accounts for 25% of the total mass of the composite water reducer; the expansion agent is shared by wheat flour and bentonite; the foaming agent is shared by zinc stearate and chromium stearate; the foaming promoter is stearic acid; the Al2O3 content in the alumina sol is 35%, and the pH value is 7.5.
[0116] 2.1 Preparation of high temperature foamed ceramic balls
[0117] The preparation method of high temperature foamed ceramic balls is as follows:
[0118] S1. Take 50% of a mixture of kaolin and mullite, 25% of a mixture of silica powder and alumina powder, 15% of a mixture of silicate cement, alumina cement and magnesia cement, 3% of a mixture of montmorillonite clay and high-iron clay, 2% of sodium lauryl sulfate, 3% of a mixture of calcium carbonate, sodium carbonate and potassium carbonate, and 2% of a mixture of silica powder and kyanite powder, stir and mix them evenly to obtain a dry material;
[0119] S2, adding water with a weight of 45% of the total weight of the dry material to the dry material, and granulating it through a drum granulator to obtain a ceramic ball body;
[0120] S3, after the ceramic ball blank is air-dried and solidified, it is sieved using a sieve to obtain a prefabricated ceramic ball blank with a particle size of 3 to 4 mm;
[0121] S4. Coat a low-melting-point glass powder ceramic coating on the surface of the preformed ceramic ball blank, wherein the components of the low-melting-point glass powder coating include SiO2, P2O5, B2O3, Li2O, ZnO, BaO, K2O, and Na2O, with a melting point of 600°C and a thickness of 40 to 50 μm; then sinter at 450°C for 4 hours, slowly cool, and sieve to obtain a high-temperature foamed ceramic ball with a particle size of 3 to 4 mm.
[0122] 2.2 High and low temperature adaptive foamed ceramic castable
[0123] 2.2.1 Composition of high and low temperature adaptive foamed ceramic castables
[0124] The high and low temperature adaptive foamed ceramic castable includes the following components in percentage by mass: 30% of high temperature foamed ceramic balls, 10% of alumina hollow balls, 12% of mullite aggregate, 1% of silicon micropowder, 1% of magnesium oxide micropowder, 1% of alumina micropowder, 3% of modified chopped alumina fiber, 1% of kyanite powder, 1% of talc fine powder, 2% of nano-silica aerogel powder, 3% of bauxite powder, 3% of calcium aluminate cement powder, 2% of mullite microporous homogenizer, 0.6% of phosphate binder, 0.6%- of fly ash, 0.7% of dispersant, 0.3% of composite water reducer, 1% of expansion agent, 2.5% of foaming agent, 0.3% of foaming promoter, 12% of nano-alumina sol and 12% of water.
[0125] 2.2.2 Preparation of high and low temperature adaptive foamed ceramic castables
[0126] The preparation method of high and low temperature adaptive foamed ceramic casting material comprises the following steps:
[0127] Step 1: Mix high-temperature foamed ceramic balls, hollow alumina balls, mullite aggregate, silicon powder, magnesium oxide powder, alumina powder, modified chopped alumina fiber, kyanite powder, talc powder, bauxite powder, and calcium aluminate cement powder in proportion, add them into a roller mixer and mix for 5 hours to obtain a mixed dry material.
[0128] Step 2: Mix the nano-alumina sol, water and nano-silicon dioxide aerogel powder in proportion, add the mixture into a planetary mixer and mix for 2.5 hours to obtain a mixed liquid;
[0129] Step 3: While the mixed solution in step 2 is being continuously stirred, the mixed dry material in step 1, the mullite microporous homogenizing material, the phosphate binder, the fly ash, the dispersant, the composite water reducing agent, the expansion agent, the foaming agent, and the foaming promoter are sequentially added to the mixed solution, and the mixture is continuously mixed in a planetary mixer for 8 hours to obtain a fluidized casting material;
[0130] Step 4: Pour the fluid casting material into the electromagnetic coil skeleton to encapsulate the coil, solidify it at room temperature for 48 hours, and place the encapsulated coil in an oven for drying and foaming. Specifically, the encapsulated coil is placed in an oven for segmented heating treatment. The temperature of the oven is set to 100°C in the first section, and the insulation time is 1.8h; the temperature of the oven is set to 180°C in the second section, and the insulation time is 4h; the temperature of the oven is set to 300°C in the third section, and the insulation time is 4h; the heating rate of the oven is 8°C / min; the encapsulated casting material is obtained.
[0131] Example 3
[0132] In this embodiment, the composite water reducer is a mixture of sodium tripolyphosphate, sodium silicate and sodium hexametaphosphate, wherein the mass of sodium tripolyphosphate accounts for 55% of the total mass of the composite water reducer, the mass of sodium silicate accounts for 30% of the total mass of the composite water reducer, and the mass of sodium hexametaphosphate accounts for 15% of the total mass of the composite water reducer; the expander is wheat flour and alum; the foaming agent is zinc stearate, chromium stearate and barium stearate; the foaming promoter is stearic acid, lead diethylguanidine phthalate and stearic acid; the Al2O3 content in the alumina sol is 40%, and the pH value is 8.5.
[0133] 3.1 Preparation of high temperature foamed ceramic balls
[0134] The preparation method of high temperature foamed ceramic balls is as follows:
[0135] S1. Take 48% of a mixture of kaolin, mullite and high-alumina bauxite, 32% of a mixture of silica powder, alumina powder and zirconium oxide powder, 12% of a mixture of silicate cement, alumina cement and water glass, 2.5% of a mixture of montmorillonite clay, bentonite and high-iron clay, 2.5% of a mixture of triethylhexyl phosphoric acid and sodium lauryl sulfate, 1.5% of a mixture of calcium carbonate, sodium carbonate, potassium carbonate and sodium chloride, and 1.5% of a mixture of silica powder, kyanite powder and clay, and stir and mix them evenly to obtain a dry material.
[0136] S2, adding water with a weight of 30% of the total weight of the dry material to the dry material, and granulating it through a spray drying granulator to obtain a ceramic ball body;
[0137] S3, after the ceramic ball blank is air-dried and solidified, it is sieved using a sieve to obtain a prefabricated ceramic ball blank with a particle size of 4 to 5 mm;
[0138] S4. Coat a low-melting-point glass powder ceramic coating on the surface of the preformed ceramic ball blank, wherein the components of the low-melting-point glass powder coating include SiO2, P2O5, B2O3, Li2O, ZnO, BaO, K2O, and Na2O, with a melting point of 800°C and a thickness of 50 to 80 μm; then sinter at 500°C for 6 hours, slowly cool, and sieve to obtain a high-temperature foamed ceramic ball with a particle size of 4 to 5 mm.
[0139] 3.2 High and low temperature adaptive foamed ceramic castable
[0140] 3.2.1 Composition of high and low temperature adaptive foamed ceramic castables
[0141] The high and low temperature adaptive foamed ceramic castable includes the following components in percentage by mass: 32% of high temperature foamed ceramic balls, 11% of hollow alumina balls, 11% of mullite aggregate, 1.5% of silicon micropowder, 1.5% of magnesium oxide micropowder, 1% of alumina micropowder, 3.5% of modified chopped alumina fiber, 1.2% of kyanite powder, 1.3% of talc fine powder, 1.5% of nano-silica aerogel powder, 1.5% of bauxite powder, 2.5% of calcium aluminate cement powder, 1.5% of mullite microporous homogenizer, 0.8% of phosphate binder, 0.8%-, 0.6% of fly ash, 0.4% of dispersant, 0.4% of composite water reducer, 2.5% of expansion agent, 1.5% of foaming agent, 0.4% of foaming promoter, 11% of nano-alumina sol and 11% of water.
[0142] 3.2.2 Preparation of high and low temperature adaptive foamed ceramic castables
[0143] The preparation method of high and low temperature adaptive foamed ceramic casting material comprises the following steps:
[0144] Step 1: Mix high-temperature foamed ceramic balls, hollow alumina balls, mullite aggregate, silicon powder, magnesium oxide powder, alumina powder, modified chopped alumina fiber, kyanite powder, talc powder, bauxite powder, and calcium aluminate cement powder in proportion, add them into a roller mixer and mix for 6 hours to obtain a mixed dry material.
[0145] Step 2: Mix the nano-alumina sol, water and nano-silicon dioxide aerogel powder in proportion, add the mixture into a planetary mixer and mix for 3 hours to obtain a mixed liquid;
[0146] Step 3: While the mixed solution in step 2 is being continuously stirred, the mixed dry material in step 1, the mullite microporous homogenizing material, the phosphate binder, the fly ash, the dispersant, the composite water reducing agent, the expansion agent, the foaming agent, and the foaming promoter are sequentially added to the mixed solution, and the mixture is continuously mixed in a planetary mixer for 12 hours to obtain a fluidized casting material;
[0147] Step 4: Pour the fluid casting material into the electromagnetic coil skeleton to encapsulate the coil, solidify it at room temperature for 72 hours, and place the encapsulated coil in an oven for drying and foaming. Specifically, the encapsulated coil is placed in an oven for segmented heating treatment. The temperature of the oven is set to 120°C in the first section, and the insulation time is 2h; the temperature of the oven is set to 200°C in the second section, and the insulation time is 5h; the temperature of the oven is set to 300°C in the third section, and the insulation time is 5h; the heating rate of the oven is 9°C / min; the encapsulated casting material is obtained.
[0148] Comparative Example 1
[0149] Except that the high-temperature foamed ceramic balls were replaced with alumina balls of the same mass and particle size, the other components and operations were exactly the same as those in Part 1.2 of Example 1 to prepare a packaged castable comparison sample 1*.
[0150] Comparative Example 2
[0151] Except for replacing the high-temperature foamed ceramic balls with hollow alumina balls of the same mass and particle size, the other components and operations are exactly the same as those in Part 1.2 of Example 1 to prepare a packaged castable comparison sample 2*.
[0152] The encapsulated casting materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested for the following performance indicators. The test results are shown in Table 1.
[0153] Bulk density: The bulk density of the castable is tested according to YB / T 5200-1993 "Test method for apparent porosity and bulk density of dense refractory castables".
[0154] Thermal conductivity: According to GB / T 2999-2016 "Test method for thermal conductivity, specific heat and diffusion coefficient of refractory materials (hot wire method)", the thermal conductivity of the castable is tested.
[0155] Table 1 Test results of performance of encapsulated casting materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2
[0156]
[0157] From the test data of the above Examples 1 to 3 and Comparative Examples 1 to 2, it can be seen that the volume density of the high and low temperature adaptive foamed ceramic castable provided by the present invention is ≤1.45g·cm -3 (450℃), ≤1.22g·cm -3 (1000℃), with good thermal insulation and high-temperature working performance, it can effectively inhibit the generation and diffusion of cracks at the sealing joint, and ensure the safety of the electromagnetic coil in this temperature range. Compared with Example 1, Comparative Example 1 replaces the high-temperature foamed ceramic balls in Example 1 with alumina balls of the same mass and the same particle size, and Comparative Example 2 replaces the high-temperature foamed ceramic balls in Example 1 with hollow alumina balls of the same mass and the same particle size. The encapsulated coils all crack at a high temperature of 1000℃, indicating that the high-temperature foamed ceramic balls in the present invention play an important role in improving the high-temperature working performance of the castable.
[0158] In summary, the present invention effectively overcomes various shortcomings of the prior art and has high industrial utilization value.
[0159] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A high and low temperature adaptive foamed ceramic castable, characterized in that: The invention comprises the following components by mass percentage: 30% to 45% high temperature foamed ceramic balls, 10% to 25% hollow alumina balls, 10% to 25% mullite aggregate, 1% to 5% silicon micropowder, 1% to 5% magnesium oxide micropowder, 1% to 5% alumina micropowder, 3% to 8% modified short chopped alumina fibers, 1% to 5% kyanite powder, 1% to 3% talc powder, 1% to 3% nano silicon dioxide aerogel powder, 1% to 3% aluminum alum. Soil powder 1%-5%, calcium aluminate cement powder 2%-5%, mullite microporous homogenizer 1%-5%, phosphate binder 0.5%-0.8%, fly ash 0.5%-1%, dispersant 0.5%-1%, composite water reducer 0.5%-1%, expansion agent 1%-5%, foaming agent 1%-3%, foaming promoter 0.1%-0.5%, nano alumina sol 10%-30%, water 10%-20%.
2. The high and low temperature adaptive foamed ceramic castable according to claim 1, characterized in that: The high-temperature foamed ceramic ball comprises a high-temperature foamed ceramic ball core and a low-melting-point glass powder coating coated on the surface of the high-temperature foamed ceramic ball core. When the ambient temperature is lower than 500°C, the structure is stable. When the ambient temperature is higher than 500°C, the high-temperature foamed ceramic ball core can foam and expand into porous microspheres, and the low-melting-point glass powder coating melts and blocks the pores on the surface of the porous microspheres.
3. The high and low temperature adaptive foamed ceramic castable according to claim 1, characterized in that: The particle size of the high temperature foamed ceramic balls is 1 to 6 mm.
4. The high and low temperature adaptive foamed ceramic castable according to claim 2 or 3, characterized in that: The preparation method of the high temperature foamed ceramic ball comprises the following steps: S1. Take 40% to 75% of refractory aggregate, 25% to 45% of reinforcing agent, 10% to 15% of adhesive, 2% to 5% of plasticizer, 1% to 3% of dispersant, 1% to 3% of foaming agent, and 1% to 5% of expansion agent by mass percentage, mix well, and obtain dry material; S2, adding water to the dry material, granulating, and obtaining a ceramic ball body; S3, air-drying and solidifying the ceramic ball blank, and screening to obtain a prefabricated ceramic ball blank; S4, coating the surface of the prefabricated ceramic ball blank with a low melting point glass powder coating, sintering, and slowly cooling to obtain a high temperature foamed ceramic ball.
5. The high and low temperature adaptive foamed ceramic castable according to claim 4, characterized in that: The preparation method of the high temperature foamed ceramic ball also includes one or more of the following features: a. The refractory aggregate is selected from any one or more of kaolin, mullite and high-alumina bauxite; b. The reinforcing agent is selected from any one or more of silicon powder, aluminum oxide powder and zirconium oxide powder; the SiO2 content of the silicon powder is ≥90wt% and the particle size is 5 to 10μm; the MgO content of the magnesium oxide powder is ≥90wt% and the particle size is 5 to 10μm; the ZrO content of the zirconium oxide powder is ≥90wt% and the particle size is 5 to 10μm; c. The adhesive is selected from any one or more of Portland cement, alumina cement, magnesia cement and water glass; d. The plasticizer is selected from any one or more of montmorillonite clay, bentonite, and high iron clay; e. The dispersant is selected from any one or more of triethylhexyl phosphate and sodium lauryl sulfate; f. The foaming agent is selected from any one or more of calcium carbonate, sodium carbonate, potassium carbonate and sodium chloride; g. The expansion agent is selected from any one or more of silica powder, kyanite powder and clay; h. In S2, the mass of water added is 35% to 55% of the total mass of dry materials obtained in S1; i. In S2, the granulation can be carried out by any one of an extrusion granulator, a drum granulator, and a spray drying granulator; j. In S3, the particle size of the sieved particles is required to be 1 to 6 mm; k. In S4, the components of the low-melting-point glass powder coating include SiO2, P2O5, B2O3, Li2O, ZnO, BaO, K2O, and Na2O, with a melting point of 500 to 800°C and a thickness of 30 to 80 μm; 1. In S4, the sintering temperature is 450-500°C and the sintering time is 3-6 hours.
6. The high and low temperature adaptive foamed ceramic castable according to any one of claims 1 to 5, characterized in that: Includes one or more of the following characteristics: (1) The Al2O3 content of the alumina hollow sphere is ≥95wt% and the sphere diameter is 0.5-1mm; (2) The mullite aggregate has a particle size of 2 to 3 mm and an average pore diameter of ≤5 μm; (3) The SiO2 content of the silicon micropowder is ≥90wt% and the particle size is 5 to 10 μm; (4) The magnesium oxide powder has a MgO content of ≥90 wt % and a particle size of 5 to 10 μm; (5) The Al2O3 content of the alumina powder is ≥90wt%, the particle size is 5-10μm, and the crystal phase is α-Al2O 3; (6) The length of the modified short chopped alumina fiber is 2 to 3 mm, and the surface is modified by KH-560 silane coupling agent; (7) The particle size of the kyanite powder is 0.5 to 1 mm; (8) The particle size of the talc fine powder is 10 to 30 μm; (9) The density of the nano-silicon dioxide aerogel powder is 0.03 to 0.08 g / cm 3 ; (10) The Al2O3 content of the bauxite powder is ≥80wt%, and the particle size is 20-45μm; (11) The calcium aluminate cement powder is obtained by high-purity calcium oxide and aluminum oxide through high-temperature sintering, and the aluminum oxide content is 80-85%; (12) The particle size of the mullite microporous homogenized material is 5 to 10 μm; (13) The particle size of the phosphate binder is 0.2 to 0.5 mm; (14) The particle size of the fly ash is 0.2 to 0.5 mm; (15) The dispersant is selected from one or a combination of triethylhexyl phosphate and sodium dodecyl sulfate; (16) The composite water reducer is a mixture of sodium tripolyphosphate, sodium silicate and sodium hexametaphosphate, wherein the mass of sodium tripolyphosphate accounts for 40-60% of the total mass of the composite water reducer, the mass of sodium silicate accounts for 20-40% of the total mass of the composite water reducer, and the mass of sodium hexametaphosphate accounts for 10-30% of the total mass of the composite water reducer; (17) The swelling agent is selected from one or more combinations of wheat flour, bentonite and alum; (18) The foaming agent is selected from one or more combinations of zinc stearate, chromium stearate, and barium stearate; (19) The Al2O3 content in the alumina sol is 30% to 40%, and the pH value is 7.0 to 8.
5.
7. A method for preparing a high and low temperature adaptive foamed ceramic castable according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: high temperature foamed ceramic balls, hollow alumina balls, mullite aggregate, silicon powder, magnesium oxide powder, alumina powder, modified chopped alumina fiber, kyanite powder, talc powder, bauxite powder, and calcium aluminate cement powder are mixed in proportion and stirred evenly to obtain a mixed dry material; Step 2: Mix the nano-alumina sol, water and nano-silicon dioxide aerogel powder in proportion, and stir evenly to obtain a mixed liquid; Step 3: under stirring conditions, the mixed dry material obtained in step 1, mullite microporous homogenizing material, phosphate binder, fly ash, dispersant, composite water reducing agent, expansion agent, foaming agent, and foaming promoter are sequentially added to the mixed liquid obtained in step 2, and stirred evenly to obtain a fluid casting material; Step 4: pour the flowing casting material obtained in step 3 into the electromagnetic coil skeleton to encapsulate the coil, solidify, dry and foam, and obtain the encapsulated casting material.
8. The method for preparing the high and low temperature adaptive foamed ceramic castable according to claim 7, characterized in that: Includes one or more of the following features: 1) In step 1, the stirring is carried out by using a roller mixer, and the stirring time is 3 to 6 hours; 2) In step 2, the stirring is performed using a planetary mixer for 2 to 3 hours; 3) In step 3, the stirring is carried out using a planetary mixer for a stirring time of 6 to 12 hours; 4) In step 4, the solidification is carried out at room temperature, and the solidification time is 24 to 72 hours; 5) In step 4, the drying and foaming treatment is specifically to place the encapsulated coil in an oven for staged temperature rise heat treatment; preferably, the temperature of the oven is set at 80-120°C in the first stage, and the insulation time is 1.5-2h; the temperature of the oven is set at 150-200°C in the second stage, and the insulation time is 3-5h; the temperature of the oven is set at 250-300°C in the third stage, and the insulation time is 3-5h; the heating rate of the oven is not higher than 10°C / min.
9. An electromagnetic coil, characterized in that: The method is packaged using the high and low temperature adaptive foamed ceramic casting material as described in any one of claims 1 to 5.
10. The electromagnetic coil according to claim 9, characterized in that The electromagnetic coils include electromagnetic coils for nuclear power control rod drive mechanisms, electromagnetic coils for aerospace engines, excitation coils and electromagnetic coils for aerospace sensors.
Citation Information
Patent Citations
Light thermal-shield refractory castable
CN101792294A
High-strength polylight mullite microporous castable and preparation method thereof
CN118290170A
Novel foamed ceramic and preparation method thereof
CN118812240A